Solve the system of equations using the elimination method and give your answer as an ordered pair:
2x + 10y = -42
-3x + 9y = -81
Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
depending on which you want to eliminate first, either x or y, doesn't matter
In this case I want to eliminate x first to find y
to eliminate x in two equation, you need to have the same coeficient of x. rite now, the 1st one has 2 and 2nd one has -3
to make them equal, you need to multiply the 1st equation with 3, and the 2nd one with 2
note that once you multiply the equation with a number, you will need to multiply it to every variable of the equation
So multiply 1st one with 3 and 2nd one with 2, you have
6x + 30y = -126
-6x + 18y = -162
now they have the same coefficient of x, you can add two equation together to have:
(6x + (-6x) + (30y + 18y) = -126 + (-162)
=> 0x + 48y = -288
-> y = -288/48
-> y = 6
now you can plug y=6 back to equation 1 or 2, doesn't matter
I plug y=6 back into the 1st equation to get:
2x + 10y = -42
-> 2x +10*6 = -42
->2x + 60 = -42
->2x = -102
->x = -102/2
final answer: x=-52 and y = 6
plug these results back to the two equations, you will see that the results satisfy the two equation